Serious Game Platform as a Possibility for Home-Based Telerehabilitation for Individuals With Cerebral Palsy During COVID-19 Quarantine – A Cross-Sectional Pilot Study - Silva, Talita Dias da; Silva, Paula Lumy da; Valenzuela, Elisa de Jesus; Dias, Eduardo Dati; Simcsik, Amanda Orasmo; de Carvalho, Mariana Giovanelli; Fontes, Anne Michelli Gomes Gonçalves; Alberissi, Camila Aparecida de Oliveira; Araújo, Luciano Vieira de; Brandão, Murilo Vinícius da Costa; Dawes, Helen; Monteiro, Carlos Bandeira de Mello (Frontiers in Psychology, 2021)
Introduction: There is a need to maintain rehabilitation activities and motivate movement and physical activity during quarantine in individuals with Cerebral Palsy (CP). Objective: This paper sets out to evaluate the feasibility and potential benefits of using computer serious game in a non-immersive virtual reality (VR) implemented and evaluated completely remotely in participants with CP for Home-Based Telerehabilitation during the quarantine period for COVID-19. Methods: Using a cross-sectional design, a total of 44 individuals participated in this study between March and June 2020, 22 of which had CP (14 males and 8 females, mean age = 19 years, ranging between 11-28 years) and 22 typically developing individuals, matched by age and sex to the individuals with CP. Participants practiced a coincident timing game (https://movehero.com.br/en/) and we measured movement performance and physical activity intensity using the rating of perceived exertion Borg scale. Results: All participants were able to engage with the VR therapy remotely, reported enjoying sessions, and improved performance in some practice moments. The most important result in this cross-sectional study was the significant increasing in rating of perceived exertion (through Borg scale) in both groups during practice and with CP presenting a higher rating of perceived exertion. Conclusion: children with CP enjoyed participating, were able to perform at the same level as their peers on certain activities and increased both their performance and physical activity intensity when using the game, supporting the use of serious games for this group for home therapy and interactive games.